Experimental and numerical determination of the effects of bipolar plates with different obstacle forms in PEMFC - Hazar, Hanbey; Durak, Alperen Latif; Sevinc, Huseyin (Elsevier Sci Ltd, 2025)
In this study, the objective was to enhance the current density and net power output of a fuel cell by incorporating obstacles of varying geometric shapes, numbers, and heights into the flow channels of bipolar plates (BP). The results demonstrated that the inclusion of obstacles in the BPs increased both the current and power density of the cell, as well as the pressure drop. Specifically, the output power of the fuel cell model with a cathode plate featuring the improved obstacle design was found to be 8.58 % higher than that of the standard serpentine model at 0.4 V. Experimentally, this increase was measured at 7.1 %. Through further analysis, the obstacle configurations that achieved the highest net power output under the specified conditions were identified, and detailed images of the pressure, temperature, and oxygen mass distributions within the cell were obtained. Based on these findings, the BP design that maximized the highest net power output within the defined parameters was identified and subsequently manufactured. A single-cell fuel cell structure was then constructed using the fabricated BPs, experimentally tested, and current-voltage (I-V) curves were obtained. Consequently, a BP was successfully fabricated for fuel cells, capable of delivering higher power generation per unit area.
Keywords: Fuel cell; PEMFC; Flow field; Pressure drop; Cell performance; Obstacles